The EU and peacebuilding: South Sudan and the Sahel indicate that the union is rethinking its concepts but not yet changing its policies - Marco Overhaus; Mateja Peter (Stiftung Wissenschaft und Politik (SWP), 2012)
Peacebuilding - understood as a broad range of activities to solidify peace and avoid the relapse into violent conflict - has become central to the self-conception of the EU as a foreign policy actor. The concept has been making inroads into different EU policy areas such as security and defence, development cooperation, enlargement and the European Neighbourhood Policy. At the same time, the dominant approach to peacebuilding has increasingly come under fire because of its failure to produce durable peace in many countries. The European Union has reacted to these challenges by adapting its concepts, but translation of these into practice - as currently witnessed in the Sahel and the two Sudans - is proving more difficult
Keywords: 320